The The Quality of Tour Guides on Tourists’ Satisfaction in Malaysia Tourism Industry - Nurul Hasanah Binti; Ismail Halidin; Anggrecke Valentina Yuricka; Muhammad Zul Amri Izzudin; Farida Rahmany (Yayasan Literasi Sains Indonesia, 2022)
Tour guides are one of the key players in the tourism industry as intermediaries between travel agents and tourists. They have a responsibility to explain the culture and all information involving the destination. This research aims to study the service quality of tour guides on tourist satisfaction. Empirical data were gathered from a large-scale online survey with 58 national and international tourists from Malaysia and Indonesia. The result shows that tour guides’ service quality has a positive relationship with tourist satisfaction